Islamic financial literacy cycle in the family - Arna Asna Annisa (Indonesian Journal of Islamic Economics Research, 2021)
People's consumption patterns are influenced by their lifestyle and the extent of their knowledge of financial management. This study aims to analyze the pattern of Islamic financial literacy in a family. This qualitative research with a phenomenological approach uses data from as many as 62 Muslim Housewives in Salatiga City. Data analysis from the results of in-depth interviews was carried out using the ATLAS t.i application. As a result, Islamic financial literacy can be carried out with a cycle of earn, management (charity, debt, consumption, saving), and growth (investment; food self-sufficiency). The results of this study become a new discourse in defining Islamic financial literacy, especially in Muslim families. This can be used as a recommendation from OJK and KNKS on educational methods to improve Islamic financial literacy.